Analisis Penerapan Sistem Pengolelolaan Persuratan di BPMP: Balai Penjaminan Mutu Pendidikan - Solihin Ginting; Ahmad Taufik Al Afkari Siahaan; Zaim Izza Makarim; Yuci Laila Amanda Ritonga (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
The rapid progress of science and technology in the field of information and communication has had an impact on all organizational operations in the contemporary era of globalization. Delivery of information will occur more quickly with increasingly advanced technology in communication. The purpose of. implementation of a letter processing system at BPMP (Education Quality Assurance Center) which makes it easier for employees to make permits to enter and leave the company and increases the disciplinary attitude of each employee. The method used is literature study and interviews. The use case diagram lists the parties involved and discusses any systemic actions that might be taken. There are five different actors in this system: visitors, staff, administration, leadership, and archives.